2017
DOI: 10.3233/wor-172628
|View full text |Cite
|
Sign up to set email alerts
|

Don’t abandon hope all ye who enter here: The protective role of formal mentoring and learning processes on burnout in correctional officers

Abstract: Confirming previous literature's suggestions, supportive mentoring and effective socialization seem to represent job and personal resources that are protective against burnout. This study provides empirical support for this relation in the prison context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Again, school leaders play a key role because they are able to identify teachers who may need support in balancing work and family domains, as well as benefit from specific interventions. In this regard, specific training programs could help teachers to develop personal resources, such as self-esteem, self-efficacy, and courage (De Stasio et al, 2017; Farnese et al, 2017; Magnano et al, 2017; Benevene et al, 2018b,c) as well as skills needed to effectively cope with high workload and time pressure (e.g., time management, goal-setting; Richardson and Rothstein, 2008). This in turn may also improve students’ personal resources, motivation, satisfaction, and performance (Magnano et al, 2014a,b; Ripamonti et al, 2018; Santisi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Again, school leaders play a key role because they are able to identify teachers who may need support in balancing work and family domains, as well as benefit from specific interventions. In this regard, specific training programs could help teachers to develop personal resources, such as self-esteem, self-efficacy, and courage (De Stasio et al, 2017; Farnese et al, 2017; Magnano et al, 2017; Benevene et al, 2018b,c) as well as skills needed to effectively cope with high workload and time pressure (e.g., time management, goal-setting; Richardson and Rothstein, 2008). This in turn may also improve students’ personal resources, motivation, satisfaction, and performance (Magnano et al, 2014a,b; Ripamonti et al, 2018; Santisi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Castiglione et al (2017) have found that discrepancies between self-representation of the future self and the current role of correctional officers increase burnout levels, affirming that individual factors are crucial because self-representation drives thoughts, actions and emotions. Research by Farnese et al (2017) has revealed how the presence of a mentor and socialization are crucial protective factors for correctional officers just assuming the role. Last, Viotti (2016) highlighted how the relationship with inmates represents a stressful factor that negatively affects the physical, cognitive, and, above all, emotional well-being of correctional officers.…”
Section: Burnout In the Context Of The Correctional Officermentioning
confidence: 99%
“…Researchers have also shown how teacher well-being could be an important determinant of student learning outcomes and students' well-being, highlighting the importance to establish the determinants not only for teachers' negative outcomes, but also positive ones that are associated to their work (Denny et al, 2011; Converso et al, 2014; Guidetti et al, 2015). Form this perspective, the present study aims to investigate teachers' well-being within the theoretical framework of the Job Demand –Resource model (JD-R model), in which job resources are all those factors that can help employees in reducing job demands and related costs (Bakker and Demerouti, 2007; Barbieri et al, 2016; Farnese et al, 2017; Falco et al, 2018; De Carlo et al, 2019). In fact, job resources include factors capable of fostering personal growth, learning and development by providing feedback, enhancing task significance, and stimulating employees' motivation (Bakker et al, 2005; Bakker and Demerouti, 2007, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%